Strategi Transformatif Pengembangan Manajemen Pesantren di Era Modern - Mohamad Mustafid Hamdi (JIEM: Journal of Islamic Education and Manajemen, 2020)
Pesantren are expected not only to play their traditional functions, namely as a transfer of Islamic knowledge, maintenance of Islam and reproduction of the ulama', but also directed toward functionalization for the development of society as a whole through pesantren reforms so that the pesantren can survive until now. In the current millennial era, the views of pesantren are very complex, but still the measure of success is a balanced vision and mission between traditional and modern education so that human resources can live a social life in society. The success of an organization/institution requires professional management skills in managing all available supporting resources. Therefore, management is very important for a leader to master both theoretically and practically so that he can manage his organization practically and efficiently. Management can also be said as a form of activity in moving other people or leading on the basis of a predetermined goal.